2019
DOI: 10.3847/1538-4357/ab1b2a
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Study of Cosmic Proton Modulation Using AMS-02 Observations

Abstract: Since 2011 May, the Alpha Magnetic Spectrometer (AMS-02) on board the International Space Station has provided monthly cosmic proton fluxes for various low-rigidity levels (P<50 GV). These precise measurements, in terms of high time and rigidity resolution, have provided a good opportunity to study cosmic ray modulation over a wide range of rigidities, together with transient events. Subsequently, a comprehensive numerical transport model has been constructed, based on Parker's transport equation that includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 76 publications
1
12
0
Order By: Relevance
“…As we have argued, the velocity factor β gives rise to little mass/charge dependence of CR diffusion in the lowrigidity limit, i.e., R 3 GV. Similar results were also reported by other authors (Corti et al, 2019;Boschini et al, 2019;Luo et al, 2019). In all these works, albeit based on different modeling, the conclusions are driven by the availability of new important measurements: the Voyager-1 data collected outside the heliosphere, and the AMS multi-channel and monthly-resolved data, collected locally and over a significant fraction of the Solar Cycle.…”
Section: Introductionsupporting
confidence: 83%
“…As we have argued, the velocity factor β gives rise to little mass/charge dependence of CR diffusion in the lowrigidity limit, i.e., R 3 GV. Similar results were also reported by other authors (Corti et al, 2019;Boschini et al, 2019;Luo et al, 2019). In all these works, albeit based on different modeling, the conclusions are driven by the availability of new important measurements: the Voyager-1 data collected outside the heliosphere, and the AMS multi-channel and monthly-resolved data, collected locally and over a significant fraction of the Solar Cycle.…”
Section: Introductionsupporting
confidence: 83%
“…Compared with previous works, we improve the technical treatments in several aspects to reduce potential uncertainties of the analyses. For the antiproton modeling, our novel treatment is to include the charge-sign-dependent three-dimensional (3D) solar modulation model [33,34] as constrained by the time-dependent AMS-02 proton data [35]. To investigate the GCE, taking a data-driven method, we identify the background components for the γ-ray sky solely with their spectral and morphological properties as in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…A similar report was made by le Roux & Potgieter (1995) who concluded that global merged interaction regions (GMIRS) forming beyond about 10 AU were required to reproduce the full amount of GCR modulation during 1977 to 1987. The effect of such a GMIR on AMS 02 proton observations was reported and modeled by Luo et al (2019). However, for the modulation period after 2009, it is not so obvious as after 1977 and 1987, how and when these GMIRS could have developed far beyond the Earth.…”
Section: Discussionmentioning
confidence: 99%